2018
DOI: 10.7759/cureus.3269
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline in Adults Aged 65 and Older in Cumbayá, Quito, Ecuador: Prevalence and Risk Factors

Abstract: ObjectiveTo assess the prevalence of and risk factors for cognitive decline and dementia in individuals greater than 65 years of age in Cumbayá, Quito, Ecuador.MethodsThis is a cross-sectional observational study that was carried out in adults over age 65. The Mini Mental State Examination (MMSE), Ascertain Dementia Eight-Item Informant Questionnaire (AD8), and Mini Nutritional Assessment (MNA) were used to assess the cognitive status and nutritional habits of this population.ResultsA total of 144 patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Results demonstrated a significant decrease in the levels of TG, Tc and Hdl-c, and in the Hb levels in males in the plasma of patients with ad, but these were not significantly correlated with BACE1-AS levels. Previous studies have shown that high Hdl and Tc levels are positively correlated with the risk of ad (52,53), in contrast to the results of the present study. This may be due to differences in the proportions of patients with moderate to severe dementia in the ad group between the two studies; the severity of ad increases the risk of malnutrition, leading to a decrease in plasma cholesterol levels (54,55).…”
Section: Discussioncontrasting
confidence: 99%
“…Results demonstrated a significant decrease in the levels of TG, Tc and Hdl-c, and in the Hb levels in males in the plasma of patients with ad, but these were not significantly correlated with BACE1-AS levels. Previous studies have shown that high Hdl and Tc levels are positively correlated with the risk of ad (52,53), in contrast to the results of the present study. This may be due to differences in the proportions of patients with moderate to severe dementia in the ad group between the two studies; the severity of ad increases the risk of malnutrition, leading to a decrease in plasma cholesterol levels (54,55).…”
Section: Discussioncontrasting
confidence: 99%
“…Grouping papers according to inclusion age (50–59 years old, 60–69 year old, and ≥70 years old), the reported prevalence ranges from 6.5% to 34% (median = 12%; 25th percentile = 9.6%; 75th percentile = 17.65%) in the first group [ 17 , 19 , 20 , 23 , 24 , 25 , 26 , 41 , 57 , 60 , 61 , 62 , 75 , 81 ], 5.1% to 37.5% (median = 20.1%; 25th percentile = 14.2%; 75th percentile = 24.7%) in the second group [ 11 , 12 , 13 , 14 , 15 , 16 , 21 , 22 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 59 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…When grouping and analyzing the effect of sample size, we divided the studies into four groups based on the number of participants they had (<1001, 1001–2500, 2501–5000 and >5000). The reported prevalence in the first group ranged from 5.3% to 37.5% (median = 22.75%; 25th percentile = 14.9%; 75th percentile = 31.4%) [ 11 , 14 , 20 , 22 , 24 , 30 , 32 , 33 , 40 , 41 , 49 , 53 , 55 , 58 , 64 , 68 , 72 , 75 , 78 , 79 , 80 , 85 , 86 , 87 , 88 , 90 ], from 7.7% to 41% in the second group (median = 15.95%; 25th percentile = 11.60%; 75th percentile = 28.50%) [ 16 , 18 , 19 , 23 , 27 , 28 , 34 , 37 , 38 , 45 , 50 , 51 , 56 , 57 , 59 , 60 , 62 , 63 , 67 , 69 , 77 , 84 , <...>…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations